Turning Toxic Nanomaterials into a Safe and Bioactive Nanocarrier for Co-delivery of DOX/pCRISPR - Rabiee, Navid; Bagherzadeh, Mojtaba; Ghadiri, Amir Mohammad; Fatahi, Yousef; Aldhaher, Abdullah; Makvandi, Pooyan; Dinarvand, Rassoul; Jouyandeh, Maryam; Saeb, Mohammad Reza; Mozafari, Masoud; Shokouhimehr, Mohammadreza; Hamblin, Michael R; et al. (ACS applied bio materials, 2021)
Hybrid bioactive inorganic-organic carbon-based nanocomposites of reduced graphene oxide (rGO) nanosheets enlarged with multi-walled carbon nanotubes (MWCNTs) were decorated to provide a suitable space for in situ growth of CoNi2S4 and green-synthesized ZnO nanoparticles. The ensuing nanocarrier supplied π-π interactions between the DOX drug and a stabilizing agent derived from leaf extracts on the surface of ZnO nanoparticles and hydrogen bonds; gene delivery of (p)CRISPR was also facilitated by chitosan and alginate renewable macromolecules. Also, these polymers can inhibit the potential interactions between the inorganic parts and cellular membranes to reduce the potential cytotoxicity. Nanocomposite/nanocarrier analyses and sustained DOX delivery (cytotoxicity analyses on HEK-293, PC12, HepG2, and HeLa cell lines after 24, 48, and 72 h) were indicative of an acceptable cell viability of up to 91.4 and 78.8% after 48 at low and high concentrations of 0.1 and 10 μg/mL, respectively. The MTT results indicate that by addition of DOX to the nanostructures, the relative cell viability increased after 72 h of treatment; since the inorganic compartments, specifically CoNi2S4, are toxic, this is a promising route to increase the bioavailability of the nanocarrier before reaching the targeted cells. Nanosystems were tagged with (p)CRISPR for co-transfer of the drug/genes, where confocal laser scanning microscopy (CLSM) pictures of the 4',6-diamidino-2-phenylindole (DAPI) were indicative of appropriate localization of DOX into the nanostructure with effective cell and drug delivery at varied pH. Also, the intrinsic toxicity of CoNi2S4 does not affect the morphology of the cells, which is a breakthrough. Furthermore, the CLSM images of the HEK-293 and HeLa cell displayed effective transport of (p)CRISPR into the cells with an enhanced green fluorescent protein (EGFP) of up to 8.3% for the HEK-293 cell line and 21.4% for the HeLa cell line, a record. Additionally, the specific morphology of the nanosystems before and after the drug/gene transport events, via images by TEM and FESEM, revealed an intact morphology for these biopolymers and their complete degradation after long-time usage.
Keywords: oxid zinečnatý; Nanocomposites; Nanotubes, Carbon; gene delivery; Zinc Oxide; Humans; HeLa buňky; drug delivery; doxorubicin; Doxorubicin; lidé; HEK293 Cells; biomaterials; HeLa Cells; graphene; HEK293 buňky; nanotrubičky uhlíkové; pCRISPR; nanokompozity